2022
DOI: 10.1007/s12325-022-02346-4
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events Reported with Therapies Targeting the CGRP Pathway During the First 6 Months Post-launch: A Retrospective Analysis Using the FDA Adverse Events Reporting System

Abstract: Introduction: Through 2018, three calcitonin gene-related peptide pathway-targeted monoclonal antibodies (CGRP mAbs) had received US Food and Drug Administration (FDA) approval for migraine prevention: erenumab, fremanezumab, and galcanezumab. Methods: This retrospective analysis evaluated adverse events (AEs) spontaneously reported to the FDA Adverse Event Reporting System (FAERS) safety surveillance database during the first 6 months post-approval of erenumab (May 2018 to November 2018), fremanezumab (Septem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 40 publications
1
7
0
1
Order By: Relevance
“…Erenumab was generally well tolerated, and all adverse effects subsided after stopping treatment. However, mild to moderate constipation (affecting 33% of our population) and bloating (affecting 10% of our population) were common adverse effects, which is consistent with previous trials in participants with headache as well as empirical data . Of note, patients with rosacea are more likely to have gastrointestinal diseases such as irritable bowel syndrome and inflammatory bowel disorders, which could have affected our data .…”
Section: Discussionsupporting
confidence: 89%
“…Erenumab was generally well tolerated, and all adverse effects subsided after stopping treatment. However, mild to moderate constipation (affecting 33% of our population) and bloating (affecting 10% of our population) were common adverse effects, which is consistent with previous trials in participants with headache as well as empirical data . Of note, patients with rosacea are more likely to have gastrointestinal diseases such as irritable bowel syndrome and inflammatory bowel disorders, which could have affected our data .…”
Section: Discussionsupporting
confidence: 89%
“…Although the evidence provided by these studies is not considered to be of the same quality as RCTs, they are very useful in that they generally confirm the results of the RCTs regarding efficacy, tolerability, and safety, and they do so within a wide variety of international cohorts, often over longer time periods. 40 Although not consistently identified as significant issues within the clinical trials, 35,41 safety issues that have been identified based on "real-world" experience include constipation and hypertension (both primarily for erenumab) and Raynaud's phenomenon; [42][43][44][45][46] however, it appears very uncommon for these or other adverse events to necessitate discontinuation of therapy. Given the active surveillance for adverse events internationally, there is a high level of confidence that any adverse events that emerge with long-term use will be identified rapidly.…”
Section: "Real-world" Studiesmentioning
confidence: 99%
“…-Se recomienda individualizar su uso en menores de 18 años, pacientes con patología cerebrovascular o cardiovascular grave en el último año o con factores de riesgo vascular no controlados, y pacientes con enfermedad de Raynaud (sobre todo secundaria), así como evitar el erenumab en pacientes con estreñimiento grave mal controlado. En estudios de la vida real no han aparecido eventos cardiovasculares de relevancia, más allá de la advertencia sobre el efecto en la presión arterial 85,86 , que en general no supera las cifras de normalidad. Es recomendable vigilar las cifras de presión arterial, en especial con el uso de erenumab en pacientes con predisposición, los primeros 7 días tras la infiltración.…”
Section: Conclusiones Y Resumen De Las Recomendacionesunclassified